Examining Attitudes and Online Distractors in Turkish EMI Context during Emergency Remote Teaching - Keskin, Fırat; Han, Turgay (LPPM Universitas Advent Indonesia, 2023)
This study aimed to examine the attitudes of students enrolled in an English preparatory program of a Turkish state university towards the use of emergency remote teaching as a mode of distance education in the 2019-2020 COVID-19 outbreak and to reveal online distractors students experienced throughout this process. A total of 270 EFL students participated in the study; 93 of these participants were female, and 177 were male. The study employed an explanatory sequential design, in which firstly quantitative data were collected using a scale (α= .871), and then qualitative data were gathered through open-ended questions followed by semi-structured ones. The quantitative data were analyzed through descriptive and inferential statistics using SPSS software while the qualitative data were analyzed through a thematic analysis conducted by the researcher and two other experts (κ = 0.70). The results showed that the students held partially positive attitudes towards the use of emergency remote teaching as a mode of distance education. There were significant differences between the students' overall attitudes and their gender, digital literacy, technological accessibility, and perceived language success. The relationship between the online distractors students experienced during Emergency Remote Teaching and their attitudes was also discussed. The conclusions were made in light of the findings, and implications and suggestions for further research were stated.